Marine Phytophthora species can hamper conservation and restoration of vegetated coastal ecosystems - Govers, Laura L.; Man in 't Veld, Willem A.; Meffert, Johan P.; Bouma, Tjeerd J.; van Rijswick, Patricia C. J.; Heusinkveld, Jannes H. T.; Orth, Robert J.; van Katwijk, Marieke M.; van der Heide, Tjisse (Proceedings of the Royal Society B: Biological Sciences, 2016)
Phytophthora species are potent pathogens that can devastate terrestrial plants, causing billions of dollars of damage yearly to agricultural crops and harming fragile ecosystems worldwide. Yet, virtually nothing is known about the distribution and pathogenicity of their marine relatives. This is surprising, as marine plants form vital habitats in coastal zones worldwide (i.e. mangrove forests, salt marshes, seagrass beds), and disease may be an important bottleneck for the conservation and restoration of these rapidly declining ecosystems. We are the first to report on widespread infection of Phytophthora and Halophytophthora species on a common seagrass species, Zostera marina (eelgrass), across the northern Atlantic and Mediterranean. In addition, we tested the effects of Halophytophthora sp. Zostera and Phytophthora gemini on Z. marina seed germination in a full-factorial laboratory experiment under various environmental conditions. Results suggest that Phytophthora species are widespread as we found these oomycetes in eelgrass beds in six countries across the North Atlantic and Mediterranean. Infection by Halophytophthora sp. Zostera, P. gemini, or both, strongly affected sexual reproduction by reducing seed germination sixfold. Our findings have important implications for seagrass ecology, because these putative pathogens probably negatively affect ecosystem functioning, as well as current restoration and conservation efforts.